FORMULASI RASIO KINERJA KEUANGAN PEMERINTAH DAERAH DI INDONESIA PERSPEKTIF MAQASHID SYARIAH - Roby Aditiya (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to formulate ratio to measure the financial performance of local governments in Indonesia with a maqashid sharia perspective. This research is qualitative research with an exploratory approach. The results show that there are eleven elements of the ratio that can be used in measuring the financial performance of local governments in Indonesia with the maqashid sharia perspective. Objective of Individual education are measured by the ratio of education spending, the ratio of planning and research spending, the ratio of spending on human resource development, and the ratio of communication and information spending. Objective of creating justice, it is measured by the ratio of financial flexibility, functional distribution ratio, and the ratio of interest-free products. Meanwhile, objective of public interest, it is measured by budget solvency ratio, financial independence ratio, local government transfer ratio, and investment and fixed asset ratio.